2013
DOI: 10.1002/pbc.24693
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of retroperitoneal teratomas and decreased incidence of sacrococcygeal teratomas in infants with Down syndrome

Abstract: Individuals with Down syndrome (DS) have a unique profile of neoplasms, with a higher incidence of leukemias and a lower incidence of solid tumors than seen in the general population. We recently encountered two cases of infants with DS with retroperitoneal teratoma. After reviewing the literature on teratomas in DS, we found that the incidence of retroperitoneal teratomas was higher and the incidence of sacrococcygeal teratomas was lower in infants with DS than in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Surgical excision is possible even in bilateral involvement and serum AFP is a reliable method of follow-up to detect recurrence [8]. Association of Down ' s syndrome and retroperitoneal teratoma has been reported but we did not see any patient with Down's syndrome in our series [9]. Gastric teratoma constitutes less than 1% of all germ cell tumors in the pediatric age group [10].…”
Section: Discussionmentioning
confidence: 73%
“…Surgical excision is possible even in bilateral involvement and serum AFP is a reliable method of follow-up to detect recurrence [8]. Association of Down ' s syndrome and retroperitoneal teratoma has been reported but we did not see any patient with Down's syndrome in our series [9]. Gastric teratoma constitutes less than 1% of all germ cell tumors in the pediatric age group [10].…”
Section: Discussionmentioning
confidence: 73%
“…[16] Kobayashi et al reported two cases of retroperitoneal teratomas in infants with Down syndrome. [17] Stage et al reported seven infants with Down syndrome having teratomas. Out of these five were retroperitoneal in location.…”
Section: Discussionmentioning
confidence: 99%
“…Spina bifida was more common in children with cancer than among population-based controls [ 33 ]. Among solid tumors associated with Down syndrome germ cell tumors are the most described [ 40 , 41 ]. One case with renal tumor had an unspecified congenital anomaly of the foot.…”
Section: Discussionmentioning
confidence: 99%